Factors Affecting Axial Neck Pain in Palm Fruit Bunch Cutting Workers Afdeling One at PT. “X” in the District Rokan Hulu Riau Province Year 2017 - Saputra, Andi Ipaljri; Syuhaily, Abdul Azhami; Hasnah, Nur (MultiTech Publisher, 2024)
In the era of globalization and technological advances, humans are always innovating to create new things, this encourages humans to improve themselves. This research method is a descriptive analytic with a cross sectional approach carried out on workers with slaughtering fresh palm fruit bunches in Afdeling one in Rokan Hulu Regency, Riau Province in 2017. as many as 48 people. The research results were analyzed using cross-tabulated frequency distributions and then tested using Chi-Square. The results of this research, from 48 samples, show that there is a significant influence on the variables of awkward body posture/work attitude, work duration, smoking habits, height and axial neck pain in workers cutting fresh fruit bunches at PT. 'X' p-value (p=0.001; p=0.032; p=0.004) where P is smaller than the significance level (α)=5% (0.05), and there is no significant influence between body weight and neck pain axial with p value (p=0.478) where P is greater than the significance level (α)=5% (0.05). This study concluded that there was a significant influence between awkward body posture/work attitude, work duration, years of service, age, smoking habits, height and axial neck pain in fresh fruit cutting workers at PT. X, and there is no significant influence between body weight and axial neck pain in workers cutting fresh fruit bunches at PT. X.